PERLINDUNGAN HUKUM TERHADAP KORBAN PEMBUNUHAN SEBAGAI PEMBAHARUAN HUKUM PIDANA DI INDONESIA (Mazahib, 2015)
This article aims at analysing the treatment of crime victim in the criminal justice system and efforts should be made to provide legal protection for the victims of crime. It argues that the treatment of crime victims by law enforcement officers do not fully provide legal protection to the victims. Meanwhile the contruction of justice views that the perpetrators and victims want a more process oriented on the real justice by promoting reconciliantion with the provision of compensation in any form and any source. Islamic criminal law, on the other hands, recognizes a kind of punishment called as blood money (diyat) for victims of murder and torture which has been apologized by the victim or family of victim. Diyat is amount of money or properties that should be paid by the perpetrator due to the death or bodily injuries suffered by the victim. Diyat punishment, therefore, do justice to both the perpetrator and victim (or his/her family) because it promotes reconciliation between the parties.